Identification of Major Chilli Suppliers within the Pasir Mas Valley Association Utilising the Analytical Hierarchy Process (AHP) Methodology - Dwi Apriyani; Eri Cahrial; Thaufan Abiyuna Ridwan (Journal of Global Sustainable Agriculture, 2024)
The form of cooperation and collaboration between farmers and Lembah Pasir Mas is in the provision of large chilies to meet market needs at the district and inter-city levels. Farmers are tasked with supplying large chilies to LPM continuously with maximum volume. LPM never determines the amount to be supplied because it has a wide market reach and is able to absorb large quantities. However, not all supplies can be accepted, of course LPM has a grading that farmers must comply with. In the process of selecting and recruiting suppliers, LPM does not set specific standards. Therefore, anyone can be a supplier and often changes every season. The purpose of the study was to analyze the criteria and sub-criteria used in selecting suppliers and to determine the best supplier priority alternatives. The analysis method used the Analytical Hierarchy Process (AHP) with 8 expert respondents. The results showed that the Quality criterion was the highest priority with a weighted value of 0.339. Furthermore, the sub-criteria that were a priority in selecting suppliers were the speed of responding to customers with a weighted value of 0.763. The supplier priorities in order include supplier E (0.437); Supplier A (0.276); Supplier B (0.169); Supplier C (0.068); and Supplier D (0.049).